2020
DOI: 10.3855/jidc.12598
|View full text |Cite
|
Sign up to set email alerts
|

Leclercia adecarboxylata as an emerging pathogen in human infections: a 13-year retrospective analysis in Southern Hungary

Abstract: Introduction: The clinical role of Leclercia adecarboxylata as an opportunistic pathogen in the context of human infections have been highlighted by multiple published case reports, describing these bacteria as novel or emerging pathogens. Methodology: The study included L. adecarboxylata isolates and laboratory data collected, corresponding to a 13-year time period (between 1 January 2005 and 31 December 2017). Presumptively identified L. adecarboxylata isolates were re-identified using VITEK 2 Compact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…In our study, a recent exposition to an aquatic environment was identified in one patient (professional swimmer presenting with corneal abscess with keratitis), such as few cases in medical literature [9]. Until now, this bacterium was considered a low-virulence pathogen with uncertain pathogenicity in human infections [6,9,10]. In our 8 samples, L. adecarboxylata was considered as a clinically significant pathogen based on clinical presentations, except for 2 episodes (one patient with VAP and the second with UTI) when clinicians considered it as an asymptomatic carriage or colonization and they have been mistreated.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our study, a recent exposition to an aquatic environment was identified in one patient (professional swimmer presenting with corneal abscess with keratitis), such as few cases in medical literature [9]. Until now, this bacterium was considered a low-virulence pathogen with uncertain pathogenicity in human infections [6,9,10]. In our 8 samples, L. adecarboxylata was considered as a clinically significant pathogen based on clinical presentations, except for 2 episodes (one patient with VAP and the second with UTI) when clinicians considered it as an asymptomatic carriage or colonization and they have been mistreated.…”
Section: Discussionmentioning
confidence: 82%
“…L. adecarboxylata is implicated in cases which involve endocarditis [15,16], catheterrelated bacteremia [10,17,18], bacteremia and cellulitis [5,6,9,19,20], urinary tract infections [6,21], pneumonia [5,22] and bacterial peritonitis, especially in peritoneal dialysis patient [7,[11][12][13][14], which was the case for the majority of our clinical presentations. L. adecarboxylata was most often found as a monomicrobial infection in immunocompromised patients, and as part of a polymicrobial infection in immunocompetent patients [5,12].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…9 Other literature has shown 91% of isolated pathogens were pan-sensitive to tested antibiotics leaving almost 10% resistant to identified antibiotics. 13 In a laboratory study, they investigated 101 Leclercia strains to 70 antimicrobial agents. They found that L. adecarboxylata was naturally resistant to multiple antibiotics including penicillin G, oxacillin, erythromycin, ketolides, linezolid, and rifampicin.…”
Section: Figure 5 a (Left) And 5b (Right) 6-month Postoperative Radimentioning
confidence: 99%